STRATEGY DEVELOPMENT OF THE NAVAL ACADEMY WARSHIP MECHANICAL ENGINEERING STUDY PROGRAM FOR IMPROVING QUALITY OF NAVAL EDUCATION - Andry Kuswoyo; Adi Bandono; Eko Krisdiono (JOURNAL ASRO, 2021)
The Naval Academy (AAL) is one of the educational implementing units within the Indonesian Navy which is tasked with producing graduates of Indonesian Navy Officers with a Bachelor's Degree in Applied Defense. One of the study programs is the Warship Mechanical Engineering Study Program which has an A accreditation based on the decision of BAN-PT. With this achievement, it is hoped that the qualification profile of graduates can be improved with international standard abilities as a supporter of professional duties as Assistant to the Head of the Machinery Division on the Corvette Warship type Sigma class. For that we need a strategy in improving the quality of education that refers to the vision and mission of AAL. This study aims to identify the influencing factors in determining the development strategy of the Warship Mechanical Engineering Study Program, formulating alternative development strategies and determining strategic priorities along with a development roadmap. The methods used are the Borda method to calculate the weight of each factor, the SWOT method to formulate strategies and the ISM method to determine the roadmap for the next five years. The conclusion of this study is the WO strategy as the chosen strategy with nine substrates in the form of a roadmap for the Warship Mechanical Engineering Study Program which will start from 2022 to 2026. Keywords: Warship Mechanical Engineering Study Program, Borda, SWOT, ISM